Identification of Teachers' Practices and Their Barriers In Chemical Cognitive Assessment During The Early Pandemic of Covid-19 - Rokhim, Deni Ainur; Widarti, Hayuni Retno; Septiani, Maya Oki; Dzikrulloh, Muhammad Hilfi Azra (Universitas Negeri Malang, 2023)
The occurrence of the Covid-19 pandemic affected the implementation of education, where learning which was originally carried out face-to-face in the classroom, now has to turn into an online system. Limited communication between students and teachers, limited time allocation, lack of facilities and internet access are obstacles that cause teaching and learning activities cannot be carried out optimally. Learning during the pandemic also raises various problems that hinder assessment activities. Therefore, the authors conducted a study that aimed to analyze teacher practices and barriers in chemical cognitive assessment during the Covid-19 pandemic. This study uses a qualitative descriptive research method with 4 stages of research, namely preparation, data collection, data analysis, and drawing conclusions. The research subjects included 85 chemistry teachers from various districts/cities throughout East Java Province. Subject selection was carried out using criterion-based selection and sample determination using cluster sampling technique. Data were analyzed using descriptive statistical techniques. The instrument used consisted of an open and closed questionnaire via the Google Form platform. The results of the study show that learning during the pandemic creates various obstacles to cognitive assessment activities in chemistry subjects. The instrument used consisted of an open and closed questionnaire via the Google Form platform. The results of the study show that learning during the pandemic creates various obstacles to cognitive assessment activities in chemistry subjects. The instrument used consisted of an open and closed questionnaire via the Google Form platform. The results of the study show that learning during the pandemic creates various obstacles to cognitive assessment activities in chemistry subjects. Obstacles in these assessment activities include the difficulty of fulfilling accurate and valid aspects and the similarity of answers between students. In addition, the lack of motivation to learn and barriers to internet access also trigger delays in assessment activities during the distance learning period